Idea autorytetu w myśleniu pedagogicznym - Lorenzová, Jitka (Studia Edukacyjne, 2017)
The article aims to illustrate how pedagogical authority has changed against the backdrop of the developments in our concept of the relationship between children and adults. It maps out selected concepts of authority in pedagogy (the platonic, democratic and patriarchal models), follows the transformations of the parent-child relationship in a psychohistorical context, and outlines the distinctions between authority and authoritarianism. Further arguments relate to the necessity of partnership in the model of pedagogical authority and demonstrate the shift from the disciplinary to the personalizing code of education, in conjunction with Bernstein's concept of invisible pedagogy. The text also deals with the contradictions and paradoxes that characterize contemporary childhood and complicate any clear-cut notion of pedagogical authority. The conclusion is that the current ambivalence surrounding pedagogical authority requires a renewal of the debate about educational ideals, especially the humanizing goal of education in post-industrial society.